Pollen counts for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010 - Anna Plikk; Stefan Engels; Maria Fernández-Fernández; Christos Katrantsiotis; Malin E Kylander; Ludvig Löwemark; Sakari Salonen; Minna Väliranta; Karin Helmens (PANGAEA, 2025)
This dataset provides the pollen counts for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010. Counts per taxon are presented against master sequence depth (m) and age (ka BP). Non-pollen palynomorphs (NPPs) and conifer stomata were also counted from the pollen slides and these data are presented alongside the pollen counts. Note that the upper 7 samples were retrieved from a different coring location but were matched to the overall sequence as described in Salonen et al. (2018). The number of Eucalyptus spores encountered during analysis are also presented. The pollen dataset provides information on terrestrial and aquatic vegetation dynamics (Salonen et al., 2018). A total of 217 samples was analysed, with samples prepared using HCl, KOH, sieving (212 μm mesh), Na-pyrophosphate, acetolysis, and bromoform heavy-liquid treatments and counted using a light microscope (400 exttimes magnification). The samples were prepared in the laboratories of University of Amsterdam, The Netherlands, and counted in the laboratories of University of Helsinki, Finland.